هجرة المستضعفين فى ضوء القرآن الكريم )تعريف الهجرة - أسبابها – و فوائدها التربوية) إلهام شكري بن بخاري - Ilham Syukri (UIN Fatmawati Sukarno Bengkulu, 2018)
The immigration of Prophet Muhammad, otherwise known as the Hijrah, was not about running away from being killed, nor was it about fear, or a retreat from bidding the lawful or forbidding the unlawful. The Hijrah was done in obedience to what Allah had ordered. During the Hajj season, when the people gathered, the Prophet peace be upon him used to call them to Islam and say to them: “say no one is God except Allah and then you will succeed”.The Prophet was very patient with what the blasphemers had done to him. His companions tolerated many types of torture including whipping, hitting, imprisonment, burning, and execution. Yet when they gained the support and aid from Allah, it was as if they had turned into a solid rock that could not be scratched. Their pious heartbeats and their silent supplications shook the hearts and thrones of the disbelievers.Keyword: Immigration, Prophet Muhammad, Hijrah